Quality of Sleep and Psychological Distress in Glaucoma - Ogunsemi OO; Bodunde OT; Afe TO; Oyelekan AA; Shorunmu TO; Onabolu OO; Abasiubong F (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Background: People living with glaucoma are psychologically burdened because of the threat of visual loss. Therefore, understanding the psychosocial issues and quality of sleep holds important implications for the recognition, prevention, and treatment of emotional problems among people with glaucoma. This study investigated the quality of sleep and psychological distress among people with glaucoma. Methods: This was a cross-sectional study of adults recruited over a period of 12 weeks from a glaucoma clinic of a Teaching Hospital in south-west Nigeria. The quality of sleep and psychological distress were evaluated using the Pittsburgh Sleep Quality Index and General Health Questionnaire respectively. Results: Ninety-three adults with glaucoma participated in the study. The mean age was 62.33 ± 15.25 years. Fifty-seven (61.3%) of the subjects were poor sleepers while 27 (29.0%) were psychologically distressed. Psychological distress correlated with global sleep score (r = 0.399, p = 0.000), subjective sleep quality (r = 0.341, p = 0.001), sleep latency (r = 0.245, p = 0.018) and sleep disturbance (r = 0.279, p = 0.007). Conclusion: Psychological distress and sleep disturbances were common among patients with glaucoma. Concerns about these issues should be incorporated into routine clinical evaluations of patients with glaucoma.